The role of youth in maintaining mangrove trees and nature in Kedah, Malaysia - Muhammad Asyraf Mohd Fazil,; Nurin Ilyana Mohd Nazri, (Penerbit Universiti Kebangsaan Malaysia, 2024)
This article's primary goal is to emphasise how crucial it is for people to preserve the health of mangroves and their surrounding natural habitat. It strives to inform people about the enormous adverse effects of youth activity on mangrove ecosystems and how individuals, communities, and society may actively contribute to their preservation and sustainability. The article examines many dangers to mangroves that youth bring, such as deforestation, pollution, overfishing, coastal development, and climate change. The article focuses on successful conservation and restoration programs that have benefited mangrove ecosystems. Mangrove ecosystems along the coast are significant habitats that offer numerous ecological and economic advantages. This literature review evaluates recent discoveries and expert opinions to understand better how youth preserve these essential ecosystems and conserve mangroves. Significant research on youth dangers, conservation and restoration initiatives, sustainable practices, community involvement, political lobbying, and individual activities are all included in the study, along with research on the ecological significance of mangroves. According to numerous studies, Mangrove forests play a significant role in biodiversity preservation, carbon sequestration, and coastal protection.